Targeted Education ApproaCH to improve Peritoneal Dialysis Outcomes (TEACH-PD): A feasibility study. Issue 2 (March 2020) - Chow, Josephine SF; Adams, Kelly; Cho, Yeoungjee; Choi, Peter; Equinox, Keri-Lu; Figueiredo, Ana E; Hawley, Carmel M; Howard, Kirsten; Johnson, David W; Jose, Matthew D; Lee, Anna; Longergan, Maureen; et al.
Background: There is substantial variation in peritonitis rates across peritoneal dialysis (PD) units globally. This may, in part, be related to the wide variability in the content and delivery of training for PD nurse trainers and patients. Aim: The aim of this study was to test the feasibility of implementing the Targeted Education ApproaCH to improve Peritoneal Dialysis Outcomes (TEACH-PD) curriculum in real clinical practice settings. Methods: This study used mixed methods including questionnaires and semi-structured interviews (pretraining and post-training) with nurse trainers and patients to test the acceptability and usability of the PD training modules implemented in two PD units over 6 months. Quantitative data from the questionnaires were analysed descriptively. Interviews were analysed using thematic analysis. Results: Ten PD trainers and 14 incident PD patients were included. Mean training duration to complete the modules were 10.9 h (range 6–17) and 24.9 h (range 15–35), for PD trainers and patients, respectively. None of the PD patients experienced PD-related complications at 30 days follow-up. Three (21%) patients were transferred to haemodialysis due to non-PD–related complications. Ten trainers and 14 PD patients participated in the interviews. Four themes were identified including use of adult learning principles (trainers), comprehension of online modules (trainers), time to complete the modules (trainers) and patient usability of the manuals (patient). Conclusion: This TEACH-PD study has demonstrated feasibility of implementation in a real clinical setting. The outcomes of this study have informed refinement of the TEACH-PD modules prior to rigorous evaluation of its efficacy and cost-effectiveness in a large-scale study.